Independent association of left atrial function with exercise capacity in patients with preserved ejection fraction. Issue 17 (3rd July 2012) - Kusunose, Kenya; Motoki, Hirohiko; Popovic, Zoran B; Thomas, James D; Klein, Allan L; Marwick, Thomas H
Abstract : Objective: Left atrial (LA) function is an important contributor to cardiac function in a variety of disease states and especially with exercise. The purpose of this study was to assess the role of LA function in the left ventricular (LV) filling pressure (E/e') response to exercise and exercise tolerance in patients with preserved LV ejection fraction (LVEF). Methods: LA contractile function (LA strain peak negative), conduit function (LA strain peak positive), and reservoir function (LA strain total) were measured from speckle tracking in 486 patients with preserved LVEF and negative exercise echocardiography for ischaemia. Maximal exercise tolerance was expressed as the estimated metabolic equivalents (METs). Per cent predicted METs was calculated in accordance with described nomograms. Features associated with exercise capacity were sought in a multiple linear regression, and compared using standardised β. Results: Patients with increased stress E/e' had significantly lower LA strain profiles and larger LA volume than the remainder. LA strain total was strongly associated with exercise capacity in multivariate analysis (ß=0.21, p<0.001). E/e' rest was also associated with exercise capacity (ß=−0.11, p=0.001). Other independent correlates of exercise capacity were age (ß=−0.36, p<0.001), male gender (ß=0.34, p<0.001) and body mass index (ß=−0.23, p<0.001). The best predictor of per cent predicted METs was total LA strain in multivariate analysis. Conclusions: The association of reduced LA function with impaired exercise capacity was similar to that of elevated LVE/e', emphasising the role of ventriculo-atrial coupling to cardiac dysfunction with preserved LVEF.